Clinicopathological characteristics of gastric cancer patients with dermatomyositis and analysis of perioperative management: a case series study - Aimaiti, Muerzhate; Zhang, Haoyu; Aikebaier, Dilidaer; Ni, Bo; Yin, Hanlin; Dong, Zhongyi; Zhang, Yeqi; Guan, Yujing; Bai, Long; Wang, Shuchang; Xia, Xiang; Zhang, Zizhen (Frontiers in Surgery, 2023)
Abstract Background This study aimed to investigate the clinical characteristics of gastric cancer (GC) patients with dermatomyositis (DM) and summarize the perioperative outcomes. Methods The clinical and pathological data of five patients diagnosed with co-occurring DM and GC (DM-GC group) were retrospectively analyzed, who were admitted to the Department of Gastrointestinal Surgery at Ren ji Hospital, Shanghai Jiao Tong University, between January 2012 and April 2023. Their data were compared with 618 GC patients (GC-1 group) from September 2016 to August 2017 and 35 GC patients who were meticulously screened from 14,580 GC cases from January 2012 and April 2023. The matching criteria included identical gender, age, tumor location, TNM stage, and surgical procedure (7 GC patients were matched for each DM-GC patient). Results Analysis indicated that the DM-GC group comprised four female and one male patient. The female proportion was significantly higher (P=0.032) than that of GC-1 group. In DM-GC group, four DM patients were diagnosed as GC within 12 months. One DM patients was diagnosed as GC within 15 months. Among them, four patients presented with varying degrees of skin rashes, muscle weakness while one patient had elevated CK levels as the typical symptom. Similarly, the preoperative tumor markers (CA-199 and CA-125) in the DM-GC group were significantly higher than normal levels (CA-199: 100 vs. 28.6%, P=0.002; CA-125: 40 vs. 2.9%, P=0.003) compared to GC-2 group. Moreover, postoperative complication incidence and the length of hospital stay were significantly higher in the DM-GC than GC-2 group (complication rate: 40 vs. 8.6%, P=0.047; hospital stay: 15 days [range: 9-28] vs. 9 days [range: 8-10], P=0.021). Conclusion GC Patients with dermatomyositis are more prone to experience postoperative complications and longer hospital stay.